Pencegahan dekalsifikasi email setelah perawatan ortodonsi - Eddy H. Habar (Journal of Dentomaxillofacial Science, 2009)
Enamel decalcification around and under orthodontic appliances have been known asa significant clinical problem, in fact an orthodontic patient is a high risk person.Whether this high risk due to oral hygiene related to orthodontic appliance or as acause of phosporic acid contained in zinc oxyphosphate cement that have beencommonly used to bracket adhesion. The purpose of this article was to provide adescription of enamel decalcification process and prevention of decalcificationfollowing orthodontic treatment. Prevention of enamel decalcification followingorthodontic treatment can be performed by polishing tooth surface after treatment,using tooth paste contained fluoride, rinsing, maintenance good oral hygiene, toothbrushing, and other additional oral hygiene method.